Records of interesting scythridids from Morocco, with description of Scythris scutulella Nupponen, sp. n. (Lepidoptera: Scythrididae) - Nupponen, Kari; Kullberg, Jaakko (Entomologica Fennica, 2013)
Recent records of eight little known species of the family Scythrididae from Morocco are presented. The material was collected during two trips in mid-May 2010 and 2011. Scythris scutulella Nupponen, sp. n. is described. The previously unknown female genitalia of S. maculosa Bengtsson, 1997 are illustrated and described, and four species are reported as new to the Maghreb area. The known distribution range of each species is given.